Tragedia i granice pesymizmu w starożytnej i współczesnej realistycznej myśli politycznej - Humphries, Carl (In Gremium. Studies in History, Culture and Politics, 2020)
This article explores the question of what we might discover about the nature and significance of contemporary forms of so-called “political realism” – particularly with regard to their relationship to pessimism – from a philosophical consideration of Ancient Greek tragedy on the one hand, and of such supposed ancient precursors of this way of thinking about ethical and/or political matters as Thucydides on the other. The principal thesis put forward here will be that Greek tragedy can prompt us to notice a revealing equivocation within the thinking of prominent recent and contemporary exponents of such realism, connected with what, in practice, it means to withhold assent from forms of morality-centred optimism on the grounds that they are perceived to be dogmatic or speculative. Such political realism, I conclude, when thus formulated, implicitly involves elements that are dogmatically pessimistic, even when expressly aspiring to be anti-dogmatic themselves. In order to clarify the significance of this equivocation, I draw a parallel with some issues that have emerged in the context of the reception of Wittgenstein’s later philosophy.